Diagnosis and treatment of interstitial cystitis - literature review - Siedlak, Agnieszka; Kułakowska, Aleksandra; Lepczyński, Bartłomiej; Kłakowicz, Philip; Lechowski, Sebastian (Journal of Education, Health and Sport, 2023)
Interstitial cystitis (IC) also known as bladder pain syndrome (BPS) is the presence of chronic or recurrent pain, feelings of tightness or discomfort perceived as associated with the bladder, accompanied by at least one lower urinary tract symptom in the absence of infection or other identifiable causes [1]. These symptoms are pain or burning while urinating; frequent urination; feeling the need to urinate despite having an empty bladder; bloody urine; pressure or cramping in the groin or lower abdomen. There is no laboratory test to make a diagnosis, it is often a diagnosis based on the exclusion of other diseases, one of the diagnostic methods is cystoscopy with the collection of specimens from the bladder and their histopathological examination [2]. Currently there is no causal treatment, only symptomatic treatment is used, such as intravesical administration of hyaluronic acid or surgical methods.